Mobile UM map (Chat Room Module) / Chew Shong Khing - Chew, Shong Khing (2006)
In this project, the system that being developed is called Mobile UM Map. There are two main parts of the system, which are map system and chat room system. The map system will allow the users to browse the University of Malaya (UM) map and search the path from one location to another location within the campus. While the chat room system allow the multi-users to carry out the discussion on the current issue that occurred within the campus. The whole application will be running in the mobile phone which fulfills the minimum requirements which is Nokia Series 60. In the whole report, all the explanations and descriptions will be emphasize on the chat room module. The objective of the chat room module in the Mobile UM Map is to allow the user to familiarize the UM environments. By using the chat room system in the application, the UM students and staffs will be able to keep alert on the latest new or activities that carried out within the campus. They will be able to feel that they are part of the family in the UM campus. The Mobile UM Map is the mobile application which will consists of mobile client, server and database. In developing the Mobile UM Map, the programming language that used to develop the mobile client is J2ME. For development of the server part is J2EE Servlet and the database that being chosen is MySQL database. The tool that used to develop the whole applications is Eclipse.